EVALUATION OF THE MORPHOLOGY AND STRUCTURE OF E GLASS FIBER-REINFORCED COMPOSITES FOR CRANIO-FACIAL BONE RECONSTRUCTION - LAZĂR, Mădălina-Anca; ROTARU, Horaţiu; PRODAN, Doina; ARMENCEA, Gabriel; BERE, Paul; ROMAN, Călin Rareș; CÂMPIAN, Radu Septimiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
New E-glass fiber reinforced composites developed to serve cranio-facial bone reconstruction were investigated using scanning electron microscopy, atomic force microscopy and X ray diffraction to evaluate their morphology and structure. The morphological analysis of the external surface of experimental composite materials has shown that the reinforcing material was well incorporated in the polymer matrix and no monofilaments of fiber glass could be observed on the material surface. Structure analysis of the experimental composites revealed the optimal interfacial adhesion obtained using A 174 silane. Woven E glass fibers were more favourable than unidirectional fibers for manufacturing cranio-facial implants. The flexural strength of the experimental composite materials was directly influenced by the degree of reinforcement. Taking into account the obtained results, the perspective of continuing the studies appears for improving the mechanical properties so as to be as close as possible to the ones of the human bone.